Analysis of Daytime Sleepiniess in adolescents by the Pediatric Daytime Sleepiness Scale: A systematic review - Meyer C.* (2017)
© 2017 Sociedade de Pediatria de São Paulo. Published by Zeppelini Publishers.Objective: To systematically review the use of the Pediatric Daytime Sleepiness Scale (PDSS) in the analysis of daytime sleepiness in children and adolescents. Data source: The electronic databases PubMed and SciELO were consulted between 2003 and 2015. As inclusion criterion, studies were considered in English, Spanish and Portuguese, original articles of any type of design, articles with a sample of children and/or adolescents, articles that used the PDSS. Duplicate articles, articles with no relation to the theme, articles with another investigated population, and articles that the parents answered the instrument for their children were excluded. To find the material with these features, the terms "Daytime sleepiness" AND "adolescents" and "Daytime sleepiness" AND "children" were used in the searches. In addition, the descriptor "Pediatric Daytime Sleepiness Scale" was used to filter more specifically. Data synthesis: Initially, 986 studies related to daytime sleepiness were identified. Considering the inclusion criteria, we analyzed 26 studies composed of 18,458 subjects aged 0 to 37 years. The diurnal sleepiness score ranged from 6.7±0.6 to 25.7±0.6 points. In general, all included studies investigated other sleep variables in addition to daytime sleepiness, such as: sleep duration, sleep quality, sleep hygiene or sleep disorders (narcolepsy and cataplexy), respiratory disorders, neurological and developmental disorders. Conclusions: There was a moderate use of PDSS to evaluate daytime sleepiness. This instrument allows the monitoring of factors that influence excessive daytime sleepiness in children and adolescents.